An atypical case of pulmonary embolism from a jugular vein. Issue 4 (December 2018) - Velcea, A E; Baldea, S Mihaila; Muraru, D; Badano, L P; Vinereanu, D
Summary: Neck venous malformations and their potentially life-threatening complications are rarely reported in the available literature. Cases of aneurysmal or hypo-plastic jugular vein thrombosis associated with systemic embolization have not been frequently reported. We present the case of a 60-year-old male, without any known risk factors for thromboembolic disease, admitted for sudden onset dyspnea. The physical examination was remarkable for a right lateral cervical mass, expanding with Valsalva maneuver. Thoracic CT with contrast established the diagnosis of bilateral pulmonary embolism and raised the suspicion of superior vena cava and right atrial thrombosis. Bedside transthoracic echocardiography confirmed the presence of a large right atrial thrombus, with intermittent protrusion through the tricuspid valve. Systemic thrombolysis with Alteplase was initiated shortly after diagnosis, in parallel with unfractionated heparin, with complete resolution of the intracavitary thrombus documented by echocardiography. The patient showed significant improvement in symptoms and was later started on oral anticoagulation. Computed vascular tomography of the neck was performed before discharge, showing hypoplasia of the left internal jugular vein and aneurismal dilation of the contralateral internal jugular vein, without thrombosis. There were no identifiable systemic causes for thrombosis. Surgical resection of the aneurismal jugular vein was excluded, because of its potential to cause intracranial hypertension. The preferred therapeutic option in this case was long-term oral anticoagulation. Learning points: Internal jugular venous malformations, such as aneurisms or hypoplasia, could be associated with an increased risk of thrombosis and major embolic events. Systemic thrombolysis can be an efficient solution in cases of pulmonary embolism with right heart thrombosis. Multimodality imaging is greatly valuable in clarifying the diagnosis of atypical cases.